Faktor-Faktor yang Mempengaruhi Pendapatan Pedagang di Pasar Keraton Kabupaten Tapin - Muhammad Rizke; Ahmad Yunani (PPJP ULM, 2023)
Using multiple linear regression models, I conducted this study in an effort to assess the factors that affect the income of the Keraton Market Traders in Tapin Regency. Primary data was used and collected through interviews and questionnaires. That partially significant effect is capital and working hours, while the location and length of business are not significant. And simultaneously, capital, location, working hours, length of business have a significant effect on the income of market traders at the Tapin Regency palace, and the most influential are capital, and working hours.